Implikasi Demokrasi Borjuis Dalam Kehidupan Bernegara - Nur Rohim Yunus (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2016)
State life, which currently uses a political structure, must have difficulties. The right that individuals have to own the means of production and property makes certain people the bourgeoisie, while others who are unable to become workers are, of course, hired by the bourgeoisie on their own lands and means of production. This is what has come to be known as bourgeois democracy. This research uses a qualitative analytical study using a bibliothèque approach. The findings of the study suggest that neoliberal democracy has an influence on the life of the country. It can be seen that in some countries the workers are marginalized and restrained. So it triggered a huge social disruption.Keywords: Democracy; Bourgeois; Country Abstrak:Kehidupan bernegara yang notabene menggunakan sistem demokrasi pasti memiliki permasalahan. Kebebasan yang dimiliki warga negara untuk memiliki alat produksi dan tanah menjadikan sebagian kalangan menjadi kaum borjuis, sedang kalangan lain yang tidak mampu menjadi kaum pekerja, yang tentunya dipekerjakan oleh kaum borjuis pada tanah-tanah dan alat-alat produksi yang dimilikinya. Hal inilah yang kemudian disebut sebagai Demokrasi Borjuis. Penelitian ini menggunakan penelitian dekriptif kualitatif dengan pendekatan pustaka. Hasil penelitian menyatakan bahwa Demokrasi Borjuis memberikan dampak kehidupan negara. Terlihat di beberapa negara menjadikan kaum buruh sebagai pihak tertindas dan terkekang. Sehingga menimbulkan gejolak sosial yang massif.Kata kunci: Demokrasi; Borjuis; Negara. DOI: 10.15408/sjsbs.v3i3.7864